Outcome of Negative Computed Tomographic Angiography in the Management of Gastrointestinal Bleeding at a Tertiary Centre: A Cross-sectional Study - Mohamad Izzat Arslan Che Ros; Nur Yazmin Yaacob; Nurafiqah Farhana Muhd Yazid (IIUM Press, 2024)
Non-Indexed Publication